2011
DOI: 10.1111/j.1365-2591.2011.01897.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical reproducibility of three electronic apex locators

Abstract: The clinical reproducibility of Dentaport ZX, RomiApex A-15 and Raypex 5 was confirmed with the majority of readings within the ± 1.0 mm range. However, the small number of identical zero readings suggests that EALs are not reliable as the sole means of WL determination under clinical conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 43 publications
1
18
0
2
Order By: Relevance
“…Although these devices seem promising, at the present there are no studies in the available literature evaluating the precision of the RomiApex A-15, both ex vivo and in vivo . As for the Propex II, at the present, its precision has only been evaluated ex vivo at the foramen level, with satisfactory results 6,14 . Despite being based on similar operating systems, these devices have different electronic components with distinct layouts, and the possible variations due to these differences are still unknown.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Although these devices seem promising, at the present there are no studies in the available literature evaluating the precision of the RomiApex A-15, both ex vivo and in vivo . As for the Propex II, at the present, its precision has only been evaluated ex vivo at the foramen level, with satisfactory results 6,14 . Despite being based on similar operating systems, these devices have different electronic components with distinct layouts, and the possible variations due to these differences are still unknown.…”
Section: Introductionmentioning
confidence: 92%
“…Recently launched in the market, the RomiApex A-15 (Romidan Ltd., Kyriat Ono, Israel) and the Propex II (Dentsply/Maillefer, Ballaigues, Switzerland), measure the working length by calculating the mean square root values of the impedance at two different frequencies (0.5 and 8.0 kHz), measured separately 6,13,14 . The devices compare the results obtained with reference values stored in its memories and then present the file positions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They generally concluded that it would be more objective to evaluate the accuracy of EALs in relation to the major foramen or AF, which seems to be a more reliable and reproducible land mark than the minor foramen or AC [7].…”
Section: Discussionmentioning
confidence: 99%
“…Thencefore, EALs have gained popularity in endodontics 7 . The latest EALs use the principle of alternating current impedance with the processing of two or more different frequencies [8][9][10] . Currently, one of the EALs which has presented satisfactory results is the Mini Root ZX (J. Morita Corp., Tokyo, Japan) 11 , a modified version of Root ZX from the same manufacturer 10 , which measures the impedance of two frequencies simultaneously 12 .…”
Section: Introductionmentioning
confidence: 99%